1977
DOI: 10.1536/ihj.18.277
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled, Double-Blind Study of dl-Alpha-Tocopheryl Nicotinate (Juvela-Nicotinate<sup>®</sup>) for Treatment of Symptoms in Hypertension and Cerebral Arteriosclerosis

Abstract: SUMMARYA controlled, double-blind study of effects of dl-alpha-tocopheryl nicotinate (vitamin E-nicotinate: EN) for relief of symptoms was perf ormed in 94 patients with hypertension and cerebral arteriosclerosis. Eighty-nine cases (44 cases treated with EN and 45 with inactive placebo) had completed this study, and remaining 5 cases were dropped out. Six capsules of EN (600mg) in the treated group and 6 capsules of inactive placebo in the placebo group were given daily for 4 weeks in all cases, and for 6 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Iino et al conducted a controlled, double-blind trial of Juvela-N (α-tocopheryl nicotinate) versus the placebo for the relief of subjectively assessed symptoms in patients with hypertension and cerebral atherosclerosis [39]. A total of 94 subjects were given either 600 mg/day of α-tocopheryl nicotinate or 600 mg/day of the inactive placebo, administered orally in six capsules, for 4 to 6 weeks, and 89 subjects completed the trial (44 in the α-tocopheryl nicotinate-treated group and 45 in the placebo group).…”
Section: Cardiovascularmentioning
confidence: 99%
“…Iino et al conducted a controlled, double-blind trial of Juvela-N (α-tocopheryl nicotinate) versus the placebo for the relief of subjectively assessed symptoms in patients with hypertension and cerebral atherosclerosis [39]. A total of 94 subjects were given either 600 mg/day of α-tocopheryl nicotinate or 600 mg/day of the inactive placebo, administered orally in six capsules, for 4 to 6 weeks, and 89 subjects completed the trial (44 in the α-tocopheryl nicotinate-treated group and 45 in the placebo group).…”
Section: Cardiovascularmentioning
confidence: 99%
“…Therefore, 4 trials that reported only on the indirect outcome of lipid oxidation were excluded from pooling 42–45 . A fifth trial 46 was excluded because none of the chosen lipid outcomes was identified. A sixth trial 47 was excluded because it was a pharmacokinetics study of coenzyme Q10.…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin E, being lipid soluble, is found in the body within the cellular and subcellular membrane phospholipids [14,104]. Dietary supplementation with vitamin E significantly lowers blood pressure in various rat models of essential hypertension including SHRs [105][106][107][108][109][110][111] (Figure 4) In three studies that examined the antihypertensive effect of vitamin E alone in human essential hypertensives, two reported that it lowered systolic blood pressure, while a third showed a reduction in both systolic and diastolic blood pressures [112][113][114] (Table 4). Vitamin E levels are lower in essential hypertensive patients [6,7] and in spontaneously hypertensive rats compared with their normotensive counterparts [74,68,115].…”
Section: Vitamin B6mentioning
confidence: 99%
“…Vasdev et al [111] Humans with hypertension and with hypertension and cerebral arteriosclerosis 600 mg/day oral dose for 4-6 weeks Lowered systolic, but not diastolic, blood pressure Iino et al [112] Humans with mild essential hypertension Spontaneously hypertensive rats 1 and 10 mg/kg body wt/day oral dose for 3 weeks Delayed onset of hypertension but no significant difference after 3 weeks of treatment in young animals (14-17 wks); 10-mg dose lowered systolic blood pressure in older animals (21-25 wks)…”
Section: Attenuated An Increase In Blood Pressurementioning
confidence: 99%